A spectrally splitting concentrating PV/T system using combined absorption optical filter and linear Fresnel reflector concentrator. (15th July 2021) - Han, Xinyue; Tu, Lin; Sun, Yao
Highlights: A CPV/T system with combined absorption filters and Fresnel reflector is developed. Optical performance of concentrator and receiver at different conditions is studied. Concentrated illumination distribution in PV module width at focal region uniform. 72.15% of spectral power in 650–1075 nm incidents PV module using PG + HB650 filter. PG + HB650 yields efficiency 46.77% and market value increase 54% compared PV system. Abstract: A novel spectral splitting concentrating PV/T system (CPV) based on a combined absorption optical filter and a linear Fresnel reflector concentrator is developed. The combined absorption optical filter includes a selective absorbing liquid and a solid absorption filter, acting as a band pass filter for silicon concentrator solar cells. The optical performance of both the concentrator and the hybrid receiver under different conditions is investigated through ray tracing software-LightTools. The results show that the concentrated illumination distribution within the PV module width at the focal region of the concentrator is quite uniform and 72.15% of the spectral power in the spectral band 650–1075 nm incidents the PV module using light filtering by propylene glycol (PG) and HB650. Furthermore, an indoor test of a simplified receiver is conducted to verify the effectiveness of the combined absorption filter and an energy conversion performance of the proposed spectral splitting CPV/T system is evaluated. The use of PG and HB650 combined filter produces a higher total efficiency of 46.77% and yields economic value enhancement of 54% compared to the PV only system.